QUEER OPPORTUNISM: STATE, MEDIA, AND LGBT+ RIGHTS IN THE CONTEXT OF THAI BOYS LOVE (BL) SERIES INDUSTRY - Torres, Igor Leonardo de Santana (Brazilian Creative Industries Journal, 2024)
Relations of appropriation of the image and agenda of minority groups have been increasingly frequent at different levels and contexts. This would be no different with the LGBT+ population, and was reflected in the Thai government’s support for the BL industry and their little to no attention to LGBT+ issues, especially marriage equality. Drawing on ethnographic research among BL series fans on Twitter and Telegram for nine months (between June 2021 and February 2022) and discussions about politics and media, pink money and pinkwashing, and homonationalism, I will introduce the concept of queer opportunism to name a contradictory relationship between state institutions or any others and the LGBT+ agenda based on fan discourses and the Thai state’s stance on the BL industry.